Hannah More the first Victorian - Stott, Anne (Oxford University Press, 2004)
This is the first substantial biography of More for 50 years and the first to make extensive use of her unpublished correspondence. Her remarkable career adds weight to the argument that Georgian women were increasingly active outside the allegedly private sphere of the home.